2013
DOI: 10.3928/01484834-20130529-02
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Culturally and Linguistically Diverse Nursing Students for Clinical Practice in the Health Care Setting

Abstract: The number of culturally and linguistically diverse (CALD) students seeking enrollment in higher education courses in Western countries where English is the predominant language has grown considerably in the past decade, especially in undergraduate health care courses. When enrolled in nursing courses, students are required to complete clinical placements. Such experiences can create significant challenges for CALD students where language, cultural differences, and interpretation of cultural norms complicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…The other two studies provided support programs to CALD nursing students (Harvey et al., 2013; San Miguel et al., 2006). The Preparation for Practice program (Harvey et al., 2013) was conducted on campus for 10 weeks per semester over two years. It consisted of discussion and role plays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other two studies provided support programs to CALD nursing students (Harvey et al., 2013; San Miguel et al., 2006). The Preparation for Practice program (Harvey et al., 2013) was conducted on campus for 10 weeks per semester over two years. It consisted of discussion and role plays.…”
Section: Resultsmentioning
confidence: 99%
“…school; Nallaya, 2016). The Preparation for Practice program was based on the participatory learning approach (Peyton, Moore, & Young, 2010), and was learner driven and combined the elements of peer mentoring and involvement of domestic non-CALD students as volunteers in the program (Harvey et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 27 studies, eight were rated as high quality . These studies reported clearly on the structure and outcomes of the programme.…”
Section: Resultsmentioning
confidence: 99%
“…Coaching sessions sought to correct students' communication deficits by incorporating activities including interpreting medication charts accurately and how to seek clarification from supervising clinical staff if unsure. Evidence has shown that cultural and linguistic diversity (CALD) students require higher levels of support when undertaking clinical placements to ensure they perform at the expected level (Harvey et al, 2013). The high numbers of ESL referrals to the CC became instrumental in the wider school community seeking out additional practice development strategies to support CALD students.…”
Section: Discussionmentioning
confidence: 99%